Interferometry of massive stars: the next step. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Stee, Ph.; Meilland, A.; Creevey, O. L.
Abstract: We present some new and interesting results on the complementarity between asteroseismology and interferometry, the detection of non-radial pulsations in massive stars and the possibility for evidencing differential rotation on the surface of Bn stars. We also discuss the curretn interferometric facilities, namely the Very Large Telescope Interferometer (VLTI)/AMBER, VLTI/MIDI, VLTI/PIONIER within the European Southern Observatory (ESO) context and the Center for High Angular Resolution Astronomy (CHARA) array with their current limitations. The forthcoming second-generation VLTI instruments GRAVITY and MATISSE are presented as well as the FRIEND prototype in the visible spectral domain and an update of the Navy Precision Optical Interferometer (NPOI). A conclusion is presented with a special emphasis on the foreseen difficulties for a third generation of interferometric instruments within the (budget limited) Extremely Large Telescope framework and the need for strong science cases to push a future visible beam combiner.